Ethanol Lock Therapy for the Prevention of Nontunneled Catheter‐Related Bloodstream Infection in Pediatric Patients. Issue 8 (17th February 2019) - Lopes, Bellisa Caldas; Borges, Paulo Sérgio Gomes Nogueira; Gallindo, Rodrigo Melo; Tenório, Thuanne Beatriz Silva; Machado, Lara Barreto; de Orange, Flávia Augusta
Abstract: Background: Ethanol lock therapy (ELT) has been reported as being effective in preventing central line–associated bloodstream infection (CLABSI) in tunneled (or long‐term) central venous catheters (CVCs). To the best of our knowledge, no studies have evaluated this therapy in relation to nontunneled (or short‐term) CVCs. Objective: To evaluate the effectiveness of ELT in preventing CLABSI in nontunneled CVC in pediatric patients. Methods: This randomized clinical trial was conducted with children aged 0–5 years and >2 kg in weight, in whom a double‐lumen polyurethane nontunneled CVC had been inserted. Patients with catheters inserted in an emergency situation, critically ill patients, and/or those with a history of hypersensitivity or allergic reactions to ethanol were excluded from the study. The variables evaluated were CLABSI, etiological agents, adverse events, and the mechanical effects of ethanol on the catheter (breakage and obstruction). Results: The CLABSI rate was lower in the ELT group compared with the control group ( P = 0.0177). However, when the occurrence of CLABSI was evaluated per 1000 catheter‐days, no significant difference was found between the groups ( P = 0.077). The frequency of side effects and catheter breakage was greater in the ELT group ( P = 0.0001 and P = 0.0005, respectively). Conclusions: The CLABSI rate was statistically significantly reduced in the ELT group compared with the controls, but the analysis of frequency per catheter‐day showed no significant difference between the groups. Thus, we should not recommend ELT for CLABSI prophylaxis in nontunneled polyurethane CVC, which requires further clinical trials.